2011
DOI: 10.4314/pamj.v8i1.71050
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic sensitivity pattern of <i>Staphylococcus aureus</i> from clinical isolates in a tertiary health institution in Kano, Northwestern Nigeria

Abstract: Background: The importance of Staphylococcus aureus as a persistent nosocomial and community acquired pathogen has become a global health

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
18
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
7
18
3
Order By: Relevance
“…Similar findings were seen by Gade et al study (Gade Qazi et al, 2013). Erythromycin was 56.6% sensitive similar to other studies (Onwubiko and Sadiq et al, 2011;Mazhar Salim AL-Zoubi et al, 2015;Abbas et al, 2015). …”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Similar findings were seen by Gade et al study (Gade Qazi et al, 2013). Erythromycin was 56.6% sensitive similar to other studies (Onwubiko and Sadiq et al, 2011;Mazhar Salim AL-Zoubi et al, 2015;Abbas et al, 2015). …”
Section: Resultssupporting
confidence: 88%
“…These antibiotics are ineffective in MRSA. In Onwubiko et al, study showed sensitivity of peniciilin and Amoxicillin-clavulanate to be 7.1% and 63% (Onwubiko and Sadiq et al, 2011). These findings of high resistance with beta lactam antibiotics suggest that they should not be used as empirical treatment even in MSSA.…”
Section: Resultsmentioning
confidence: 99%
“…Here taking the safety profile of Amoxicillin/clavulanate in lactating and pregnant women we choose Amoxicillin/clavulanate as antibiotic of choice for both the groups. These results were in accordance with study by Onwubiko et al13…”
supporting
confidence: 94%
“…1). Staphylococcus aureus develops resistance very quickly and successfully to different antimicrobials over a period time (Onowubiko and Sadiq, 2011). The highest frequency of Staphylococcus aureus occurred with susceptibility to antimicrobial agent cefuroxime (68%) followed by cefotaxime, cefriaxone and gentamicin (60%) while the least was tetracycline (4%).…”
Section: Susceptibility To Antibiotics Of Isolated Germsmentioning
confidence: 97%